The Postgraduate Research Methods Course in Conservation: The Practical Approach Taken at the University of Gothenburg - Elizabeth E. Peacock (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The theory-led Master’s Research Methods course in the Department of Conservation at the University of Gothenburg was completely redesigned for the 2013 autumn term from a theory-led to a student-oriented learning format. The practical techniques and interactive skills framework enables students to become familiar with common research tools culminating with each student writing a Master’s research project proposal. This article presents a reflective case study analysis of the course redesign undertaken with the aim to improve the student learning experience of research methods, and presents a model for research methods education in cultural heritage conservation.